Peranan Ahmad Surkati Dalam Gerakan Pembaharuan Islam Melalui Perhimpunan Al- Irsyad 1914-1943 - Sri Suryana (Pascasarjana Universitas Islam Negeri Raden Fatah Palembang, 2017)
Dutch power in Indonesia is being intensified with the mission of Christianization. Traditional methods of suppressing Islam are considered not capable of being a solution to various problems faced by Muslims. For this reason Ahmad Surkati came to Indonesia at Jamiat Khair's request to teach. Then there was a dispute between Ahmad Surkati and other Jamiat Khair figures. This is what causes Ahmad Surkati to leave the Khair Jamaah. Then joined the non-sayyid group to establish an Islamic organization which was given the name Al-Ershad. With the aim of renewing Muslims in Indonesia. The research method used is a qualitative descriptive method. While the types and sources of data used in the study are qualitative data that are sourced from primary and secondary data. From the results of the analysis, it can be seen that Ahmad Surkati is one of the leaders of Islamic reformers in Indonesia originating from Sudan. His arrival in Indonesia on the basis of Jamiat Khair's request as a teaching staff, namely in 1911. Later he founded the Association of Al-Ershad in 1914 as a place to carry out a movement for renewal. Ahmad Surkati's renewal ideas were much influenced by the renewal movements carried out by Muhammad Abduh and Rashid Ridha in Egypt. Among the innovations carried out by Ahmad Surkati can be identified through three fields. First, in the field of education, he modernized Al-Irsyad's education in all aspects, both institutionally, educational goals, curriculum content, methods and approaches and libraries for schools. Second, the field of da'wah, he founded idārat al-haq, and carried out da'wah with three ways of preaching at once, namely bi al-hāl, bi al-lisān and bi al-qalam. Third, the socio-religious field, he socializes the notion of equality of degrees, cooperates with other organizations to improve the condition of the ummah, and provides solutions about religious issues raised by the community.